PENGARUH GAYA HIDUP, CITRA MEREK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPATU SNEAKERS MEREK CONVERSE (Studi pada Mahasiswa Universitas Diponegoro Semarang) - Nuki Dian Marchiani; Wahyu Hidayat; Reni Shinta Dewi (Universitas Diponegoro, 2015)
This research is motivated by consumer behaviour which are varied and difficult to predict that causes the business world changes so fast. Consumers wants a products that suits their taste, lifestyle, and their needs. This leads the companies to experiencing strict competition caused by the increasingly consumer complex demands. One of the product that always follow consumer tastes is shoes. Shoes is no longer needed only for a footwear that protects feet from sharp objects, but also as a fashion product, so the design, material, and pattern became very varied. However, in the period 2009-2013 the sales of Converse sneakers shoes has fluctuated and always under Adidas, Nike and Bata.The purpose of this study was to determine the effect of lifestyle, brand imange and product quality on purchase decision of Converse sneakers shoes. This research method is explanatory, with data collection through questionnaires and interviews. The sampling technique used purposive and proportional technique sampling. The samples are 96 peoples whom are college student of Diponegoro University Semarang. The analysis technique used was qualitative and quantitative. Quantitative analysis using validity, reliability,correlation coefficient, coefficient of determination, simple and multiple regression analysis, as well as the significance test (t test and F test). The results of this study showed a relatively good level of lifestyle, brand image and product quality and high purchase decision.All independent variables, namely lifestyle (X1), brand image (X2), and product quality (X3) together (simultaneously) or individually (partial) affect purchase decision dependent variable (Y). Advice that can be given is the need to improve ways of promotion, innovate in the design of Converse sneakers that are to not assessed as monotonous and provide many options to purchases Converse sneakers shoes.